Pengaruh Ketidakpuasan Kerja terhadap Kreativitas: Studi tentang Peran Continuance Commitment dan Dukungan Fakultas dalam Konteks Organisasi: Pengaruh Ketidakpuasan Kerja terhadap Kreativitas: Studi tentang Peran Continuance Commitment dan Dukungan Fakultas dalam Konteks Organisasi - Andika Amirulhaqi; Fiona Niska Dinda Nadia; Nuri Herachwati (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This study examines the influence of job dissatisfaction on creativity, as moderated by continuance commitment and perceived organizational support for creativity. The research employs an explanatory method with a quantitative approach. The results demonstrate that job dissatisfaction has a positive and significant effect on creativity. Additionally, there is an interaction between job dissatisfaction, continuance commitment, and social support from colleagues which impacts creativity. Perceived organizational support for creativity also moderates the relationship between job dissatisfaction and creativity. This research contributes to understanding how job dissatisfaction can trigger creativity, depending on employee responses and support received from various related parties. In an organizational context, supportive colleague behaviors and perceived organizational support for creativity are critical factors in channeling job dissatisfaction towards creativity. Social support from colleagues and the organization can mitigate work stress and increase job satisfaction levels. Creativity can be fostered by establishing a supportive context. Faculties can encourage dissatisfied lecturers to engage in creative activities by providing support and fostering an environment conducive to creativity.